Rotational Distortion and Compensation in Optical Coherence Tomography with Anisotropic Pixel Resolution - Guangying Ma; Taeyoon Son; Tobiloba Adejumo; Xincheng Yao (Bioengineering, 2023)
Accurate image registration is essential for eye movement compensation in optical coherence tomography (OCT) and OCT angiography (OCTA). The spatial resolution of an OCT instrument is typically anisotropic, i.e., has different resolutions in the lateral and axial dimensions. When OCT images have anisotropic pixel resolution, residual distortion (<semantics>RD</semantics>) and false translation (<semantics>FT</semantics>) are always observed after image registration for rotational movement. In this study, <semantics>RD</semantics> and <semantics>FT</semantics> were quantitively analyzed over different degrees of rotational movement and various lateral and axial pixel resolution ratio (<semantics>RL/RA</semantics>) values. The <semantics>RD</semantics> and <semantics>FT</semantics> provide the evaluation criteria for image registration. The theoretical analysis confirmed that the <semantics>RD</semantics> and <semantics>FT</semantics> increase significantly with the rotation degree and <semantics>RL/RA</semantics>. An image resizing assisting registration (RAR) strategy was proposed for accurate image registration. The performance of direct registration (DR) and RAR for retinal OCT and OCTA images were quantitatively compared. Experimental results confirmed that unnormalized <semantics>RL/RA</semantics> causes <semantics>RD</semantics> and <semantics>FT</semantics>; RAR can effectively improve the performance of OCT and OCTA image registration and distortion compensation.